Partisipasi Orang Muda Katolik dalam Kehidupan Menggereja Stasi St.Yosef Arso VII - Novia Lidwina Eva Martina; Sinaga, Rotua Dominika (Kariwari: Jurnal Pendidikan Agama Katolik dan Pastoral, 2025)
This research is motivated by the low involvement of young Catholics in church activities at the St. Joseph Arso VII Station, especially related to the five main tasks of the Church: koinonia, liturgy, kerygma, diakonia, and martyria. The purpose of the research is to determine the forms of youth participation, identify supporting and inhibiting factors, and analyze the station's efforts to increase their involvement. This research uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that youth participation is still limited, especially in the areas of liturgy and kerygma, which is influenced by a lack of discipline, self-confidence and also mentoring from Catholic Youth mentors. Supporting factors found include support from family, school, church, and social media, while inhibiting factors include personal busyness, weak family attention, limited facilities, and the influence of digital culture. The efforts made by the St. Joseph Arso VII Station include increasing pastoral care, involving youth in categorical activities, providing facilities, and strengthening faith through spiritual meetings. This research is expected to contribute to more effective pastoral strategies and encourage young people in church life.